Analysis of Scottish tax and benefit reforms - Tom Waters; Tom Wernham (Institute for Fiscal Studies (IFS), 2023)
We analyse the impact of changes to devolved income tax rates and bands and benefits, and show the total impact of the changes.
Keywords: 330; Government finances and spending; Taxes and benefits; Scottish Budget 2023– 24; Benefits; Working age benefits; Disability; Devolved government finances; Tax